2012
DOI: 10.2147/opth.s27859
|View full text |Cite
|
Sign up to set email alerts
|

Pain and accuracy of focal laser treatment for diabetic macular edema using a retinal navigated laser (Navilas®)

Abstract: AimTo investigate treatment-related pain and the accuracy of navigated laser photocoagulation in the treatment of clinically significant macular edema.MethodsFocal laser treatment of diabetic macular edema in 54 consecutive patients was digitally planned on fundus images and performed using the navigated laser photocoagulation system Navilas® (OD-OS GmbH, Teltow, Germany). Treatment-related pain was quantified on a visual analog scale directly after treatment and compared with a matched control group who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 15 publications
(18 reference statements)
1
33
1
7
Order By: Relevance
“…The uncertainty regarding the resulting size of the laser burn may lead to unfavorable visual acuity or visual field outcome and decreases controllability of the MLP performed in the presence of a retinal edema. Our results go well along with previous studies that demonstrated a higher laser spot application accuracy focal MLP for DME [14] and a higher rate of accuracy in focal MLP treatment of DME than standard manual-technique laser treatment [15]. However, the concordance between the size of actual laser burns and that of planned laser burns has not been investigated until now, and this aspect of MLP controllability and accuracy is more important in grid MLP than in focal MLP due to a higher number of laser burns applied to the retina.…”
Section: Discussionsupporting
confidence: 91%
“…The uncertainty regarding the resulting size of the laser burn may lead to unfavorable visual acuity or visual field outcome and decreases controllability of the MLP performed in the presence of a retinal edema. Our results go well along with previous studies that demonstrated a higher laser spot application accuracy focal MLP for DME [14] and a higher rate of accuracy in focal MLP treatment of DME than standard manual-technique laser treatment [15]. However, the concordance between the size of actual laser burns and that of planned laser burns has not been investigated until now, and this aspect of MLP controllability and accuracy is more important in grid MLP than in focal MLP due to a higher number of laser burns applied to the retina.…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, patients usually report less pain, most probably because retinal sensitivity is better preserved as compared with pain in conservative approaches (9,17) . Recent studies have consistently shown that patients treated with either the PASCAL or NAVILAS laser system modalities experienced less pain as compared with those treated with conventional laser treatment modalities (9,10,17,22) . The reason why patients treated with the NAVILAS system experience less pain than those treated with the PASCAL system may in part be attributed to the fact that the former uses infrared light instead of the bright slit-lamp light used in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern scan laser (PASCAL; Opti-Medica Corp., Santa Clara, California, USA) is a new generation semi-automatic and multi-shot photocoagulator, which uses either a single or predetermined pattern array with pulse durations as short as 10-30 ms (8,9) . Navigated laser pho tocoagulation (NAVILAS; OD-OS GmbH, Teltow, Germany) is another novel computer-based double-frequency ND:YAG laser photocoagulation system (532 nm), which, apart from offering retina navigation, has similar technical specifications as PASCAL (single or prede- termined pattern array, 10-30-ms pulse duration) (10,11) . Compared with conventional lasers, both modalities use shorter laser pulses, cause relatively less thermal damage to adjacent retinal tissues and are therefore possible to produce relatively less painful photocoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…The NAVILAS system has been shown to have both a high degree of safety and combines the advantages of computerized precision and accuracy to efficiently perform focal retinal laser therapy [4-7,10,11]. Traditional focal laser therapy requires a contact lens, topical anesthesia, and the patient’s cooperation to fixate for the treatment period.…”
Section: Discussionmentioning
confidence: 99%